조각에 있어서 ‘운동성’에 관한 연구 - 노해율; Noh Hae Yul (기초조형학연구, 2021)
이 연구의 목적은 형식적, 개념적, 정치적으로만 다뤄지던 조각에 있어서 운동성에 대한 새로운 해석을 시도하는 것이다. 연구 대상은 정지된 조각에 있어서 시· 공간과 운동의 관계 그리고 조각에 있어서 운동성의 발생 원리이다. 이 연구는 20세기 전후 시간, 공간, 운동에 관한 이론적 논의들 중 베르그 손의 지속이론과 아른하임의 지각이론에 이론적 바탕에 둔다. 먼저 시간은 정지되거나 구분 지어서 생각할 수 없으며, 의식의 흐름에 의해서만 지각될 수 있음을 확인한다. 또한 운동과 부동의 실현 조건에 있어서 시· 공간이 전제된 것이 아니라, 운동을 통해서 시· 공간이 지각되는 것임을 알 수 있다. 이러한 과정에서 운동과 운동성은 필연적이지 않음을 증명하고, 결국 운동성은 사물의 운동에서 발현하는 것이 아니라 지각을 통해서 발생한다는 것을 고찰한다. 이를 통해서 미술사에서 등장하였던 조각에 나타난 ‘운동성’에 관한 다양한 사례를 확인하고, 그 양상을 세 가지 형식으로 분석한다. 첫째는 인체 조각을 통해서 나타나는 ‘운동성’이고, 둘째는 미래주의와 구조주의에서 발생한 ‘운동성’의 표현이다. 그리고 셋째는 실제적 운동을 표현한 조각이다. 조각에서 나타나는 ‘운동성’의 양태는 다섯 가지로 분류된다. 첫 번째는 생동감 있는 인체 표현이다. 두 번째는 로뎅의 인체 조각에서 나타나는 주체적 ‘운동성’의 양태이다. 세 번째는 미래주의에서 시작된 개념적 운동과 현실 운동이 결합 된 초월적 ‘운동성’이다. 네 번째 양태는 러시아 구조주의자들로부터 시작된 현실적 ‘운동성’이다. 다섯 번째 양태는 실제 운동을 통한 ‘운동성’의 발생이다. 이 연구는 운동성으로 조각의 분석이 가능함을 증명하고, 운동성이 만들어 내는 시각적 효과에 가려서 충분한 해석의 기회를 갖지 못한 다양한 장르의 조각에 대한 새로운 해석을 목적으로 하고 있다. This study aims to try new interpretation about the ‘movement’ in sculpture that has been handled formally, conceptually and politically. The subjects of the study are to consider the relationship between space-time and motion in the static sculpture, and the generating principle of movement in sculpture. This study is theoretically based on the theory of duration of Bergson and the visual perception theory of Arnheim among the theories about time, space and motion around the 20th century. First, this study verifies that time doesn’t stand still and can’t be classified, but can be perceived only by the stream of consciousness. Moreover, the implementation requirements for motion and stoppage isn’t premised on space-time, but space-time is perceived through motion. The analysis proves that motion and movement are not inevitable and that movement is not made through the motion of an object but perception. Various cases of ‘movement’ appearing in sculptures that have appeared in art history are identified, and analyzed in three forms. The first is ‘movement’ that appears through human body sculpture, and the second is the expression of ‘movement’ that arises from futurism and structuralism. And the third is a sculpture that expresses the actual motion. There are five types of ‘movement’ that appear in sculpture. The first is a lively representation of the human body. The second is the aspect of independent ‘movement’ that appears in Rodin's human body sculpture. The third is a transcendental ‘movement’ that combines the conceptual motion and the real motion that originated from futurism. The fourth aspect is a realistic ‘movement’ originating from the Russian structuralists. The fifth aspect is the generation of ‘movement’ through actual motion. In conclusion, This study verified that sculpture can be analyzed by ‘movement’ and proposed the possibility for new interpretation on various kinds of sculpture that has been buried by the visual effect of movement.